1983
DOI: 10.1104/pp.71.4.912
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glutamine Synthetase from Pea by Tabtoxinine-β-lactam

Abstract: Tabtoxinine-f-lactam, a hydrolytic product of tabtoxin produced by Pseudoonas syringae pv. tabaci, apparently inactvates pea seed glutamine synthetase. Inhibition of the enzyme's initial velocity is linear over a range of 0.5 to 5 minhmmolar tabtoxinne-/-lactam in the presence of 10 m_mlar glutamate. A method for the purification of glutamine synthetase from dried peas is presented which gives a 30% yield with a 2,000-fold Increase in specific activity. A method for obtaining highly puied tabtoxinine-f8-lactam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 7 publications
(5 reference statements)
1
50
0
1
Order By: Relevance
“…26 P. syringae pv tabaci 6605 was cultured in PY medium containing 20 µg/ mL rifampicin. 27 Purification of TβL was performed according to the method described by Tomas et al 28 Bacterial suspension, l-methionine sulfoximine (MSX; Funakoshi) and TβL were infiltrated into N. benthamiana leaves as described previously. 9 Isolation of RNA and cDNA synthesis Total RNA was isolated from N. benthamiana leaves with RNAiso (Takara), and RNA samples were treated with DNase I (RNase-free; Takara) to degrade contaminating genomic DNA as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…26 P. syringae pv tabaci 6605 was cultured in PY medium containing 20 µg/ mL rifampicin. 27 Purification of TβL was performed according to the method described by Tomas et al 28 Bacterial suspension, l-methionine sulfoximine (MSX; Funakoshi) and TβL were infiltrated into N. benthamiana leaves as described previously. 9 Isolation of RNA and cDNA synthesis Total RNA was isolated from N. benthamiana leaves with RNAiso (Takara), and RNA samples were treated with DNase I (RNase-free; Takara) to degrade contaminating genomic DNA as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…T-,-L was obtained by the method of Thomas et al (17). Attempts to recover GS activity by dialysis after inactivation were done by the methods of Maurizi and Ginsburg (7).…”
Section: Methodsmentioning
confidence: 99%
“…The physiological target in plants, glutamine synthetase (GS) (EC 6.3.2.1.) (5,6,17) is irreversibly inhibited by T-P-L (6,17). A preliminary study by Thomas and Durbin (16) showed that GS from subsp.…”
mentioning
confidence: 99%
“…Some are polypeptids, glycoproteins others are secondary metabolites that are required as virulence factors in plant disease (Alfano and Collmer, 2004). These toxins acts by using diverse mechanisms from modulating and suppressing plant defense response to alteration and inhibition of normal host cellular metabolic process (Thomas et al, 1983). These toxins act also directly on the expression and development of disease symptoms.…”
Section: Toxins (Pathotoxins)mentioning
confidence: 99%
“…These toxins act also directly on the expression and development of disease symptoms. Among the most well studied pathotoxins known also as phytotoxins include syringomycins, syringopeptins, tabtoxins, phaseolotoxins and coranotine described particularly in P. syringae pathovars (Thomas et al, 1983).…”
Section: Toxins (Pathotoxins)mentioning
confidence: 99%